The financial advisor's success manual : how to structure and grow your financial services practice - Leo, David I.; Cmiel, Craig (American Management Association, 2018)
The tools and techniques you need to be a top-producing financial advisor. How do you become a million-dollar producer, boost client satisfaction, and dramatically expand your business? The Financial Advisor's Success Manual provides the answers to these all-important questions -- along with the proven techniques and expert insights you need to maximize the profitability of your practice. Financial service firms traditionally aren't designed for serious growth. But this book shows how to break that cycle and earn more -- all while serving your clients better. You'll learn to: Develop a differentiation strategy Effectively segment your book and analyze opportunities Define and implement your six core client-facing processes Balance the cost of services with the value delivered Formulate your business plan Enhance client loyalty Measure what matters Perfect your personal marketing and sales approach Packed with tables, graphs, forms, worksheets, sample letters, and more, The Financial Advisor's Success Manual supplies everything you need to grow your business beyond your wildest expectations.